Inversor multinivel bidirecional com até 15 níveis na tensão de saída utilizando somente uma fonte CC - Nascimento, Anderson Jhones Passos (2021)
This work proposes a bidirectional asymmetric multilevel inverter with a single Direct Current(DC) source and a transformer with multiple secondaries for obtaining up to 15 levels at theoutput voltage. The suggested topology is composed by a transformer, a H-Bridge locatedat the transformer primary, and asymmetric cells associated with two bidirectional switchesat the transformer secondary. According to the weights of the AC secondary voltage sourcesand the combinations of switching states applied to the L cells, the inverter can generate upto 15 levels at the output voltage. The transformer employed works at a frequency of 60 Hz,multiple secondaries, which reduces the number of isolated voltage sources, and it operates asa high gain voltage. The inverter works with staircase modulation, whose principle is basedon the elimination of harmonics, the technique is generally applied at low switching frequencyand widely used in high power applications. The proposed topology presents low harmonicdistortion and reduced number of semiconductor switches when compared to the conventionalmultilevel converter to produce the same levels number at the output voltage. Theoretical studies,simulation and experimental results are shown in order to validate the proposed converter. A 1kW laboratory prototype was developed and implemented in laboratory and put into operation inopen loop. In order to show that the inverter is bidirectional in current, an inductance of 300 mHwas used at the inverter output, an application made in simulation, which made it possible toobserve the return of energy in the load direction to the source, could be observed. In relationto the practical performance, collected in the laboratory, the converter showed a performanceofη= 95% in the first test with 210 W and the average that the power was being increased theperformance was decreasing. This test was carried out for up to 960 W, power for which theyield presented wasη= 90%